The role of nusantara ulama’s da’wah in islamic moderation: A critique of blackwater and peripheral in Islamic studies - Sa’dullah, Sa’dullah; Hajam, Hajam (Faculty of Dakwah and Communication, Walisongo State Islamic University, 2025)
Purpose - This study aims to analyze the role of Nusantara ulama’s da’wah in promoting Islamic moderation as a response to global narratives that often marginalize peripheral Islamic traditions, as represented by the Blackwater symbol. Method - This research employs a qualitative approach using the library research method. Data were collected from various literature sources and analyzed descriptively and analytically. Result - The findings indicate that Nusantara ulama play a significant role in fostering Islamic moderation by integrating Islamic values with local wisdom. Nusantara Islam, characterized by its tolerance, inclusiveness, and flexibility, has proven to be a relevant model for Islamic moderation in global discourse. The narrative of Nusantara Islam addresses critiques of the marginalization of Southeast Asia as